The chemistry of the pedoderm – part 3: Colophospermum mopane shrublands and woodlands in the central Kruger National Park, South Africa. Issue 4 (2nd October 2022) - Mills, Anthony J; Strydom, Tercia; Allen, Jessica L; Baum, Julia
Abstract : The woody plant, Colophospermum mopane, occurs as either a shrub or tree in shrublands and woodlands, respectively, in the central Kruger National Park, South Africa. As a first step in identifying which soil properties potentially influence the structure of C. mopane in these landscapes, we investigated the soil chemistry of the pedoderm in shrublands and woodlands. A total of 39 composite pedoderm samples (0–2 cm) were analysed. Relative to the woodlands, the pedoderm of the shrublands had significantly lower mean concentrations of P, K, Ca, Mg, S, Mn, Cu, Na, B and C. Of the nutrients analysed, only B had a mean concentration likely to be constraining the growth of plants (0.16 ± 0.01 vs 0.69 ± 0.05 mg B kg −1 in shrublands and woodlands, respectively). We suggest that the C. mopane shrubs do not establish as trees in the shrublands because deficiency of B limits their growth and increases the competitive strength of the grass sward relative to eudicot plants in the landscape.